Estimation of compressive strength of high-strength concrete with recycled aggregate using non-destructive test and numerical analysis. (May 2014) - Cho, Y. S.; Baek, S. K.; Lee, Y. T.; Kim, S. H.; Hong, S. U.
<x content-type="archive" xml:space="preserve">Abstract</x> The purpose of the study is to provide reliable data on high-strength recycled aggregate concrete and basic data for maintaining a structure built with high-quality recycled aggregates. An experimental concrete structure mould with rectangular parallelepiped dimensions of 600×600×200 mm, is prepared to measure the wave velocity of specimens aged 28 days. The ultrasonic pulse velocity was measured for specimens that were aged for 1, 3, 7 and 28 days. In the compressive strength test at a material age of 28 days, the concrete incorporating recycled aggregates show almost the same or slightly lower strength compared with natural aggregate concrete. Using the variables of optimised contact time, the velocity of the compression wave obtained through simulation can be an index to determine non-destructive test reliability and evaluate the applicability.